2017
DOI: 10.1159/000471797
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antenatal Melatonin Treatment on the Cerebral Vasculature in an Ovine Model of Fetal Growth Restriction

Abstract: Chronic moderate hypoxia, such as occurs in fetal growth restriction (FGR) during gestation, compromises the blood-brain barrier (BBB) and results in structural abnormalities of the cerebral vasculature. We have previously determined the neuroprotective and antioxidant effects of maternal administration of melatonin (MLT) on growth-restricted newborn lambs. The potential of maternal MLT therapy for the treatment of cerebrovascular dysfunction-associated developmental hypoxia has also been demonstrated in newbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 64 publications
4
46
0
Order By: Relevance
“…Our results are in agreement with past studies that used fetal sheep models from pregnancies complicated by fetal growth restriction. These past studies showed that antenatal treatment with melatonin could reduce oxidative stress to decrease neurodevelopmental deficits in newborn lambs and protect their cerebral vascular endothelium to maintain the blood‐brain barrier . Furthermore, other studies have shown that melatonin administration even after an ischemic insult to the fetus, such as following hypoxia‐ischemia or brief asphyxiation via cord occlusion, can provide neuroprotection for the fetus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in agreement with past studies that used fetal sheep models from pregnancies complicated by fetal growth restriction. These past studies showed that antenatal treatment with melatonin could reduce oxidative stress to decrease neurodevelopmental deficits in newborn lambs and protect their cerebral vascular endothelium to maintain the blood‐brain barrier . Furthermore, other studies have shown that melatonin administration even after an ischemic insult to the fetus, such as following hypoxia‐ischemia or brief asphyxiation via cord occlusion, can provide neuroprotection for the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…These past studies showed that antenatal treatment with melatonin could reduce oxidative stress to decrease neurodevelopmental deficits in newborn lambs and protect their cerebral vascular endothelium to maintain the blood-brain barrier. 44,45 Furthermore, other studies have shown that melatonin administration even after an ischemic insult to the fetus, such as following hypoxiaischemia 46 or brief asphyxiation via cord occlusion, 47 can provide neuroprotection for the fetus. Our results, along with these past studies, show the plausibility of using adjuvant melatonin for the prevention and/or partial treatment of fetal neurodevelopmental deficits induced by IUI.…”
Section: Discussionmentioning
confidence: 99%
“…The similar findings in this study suggest that cerebrovascular injury results in increased vasoreactivity, ultimately reducing cerebral perfusion, as a protective effect to prevent increased injury. While the mechanism for this is unknown, it could be mediated by withdrawal of astrocyte end-feed from the blood vessel walls due to haemodynamic injury, resulting in cerebrovascular breakdown and increased leakage 34. However, more research is required to fully elucidate the cause of cerebrovascular dysfunction in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in BBB composition have been reported in IUGR neonates (Castillo‐Melendez et al . , ). Decreased BBB integrity may result in an increased infiltration of systemic inflammatory mediators into the brain, further exacerbating the neuroinflammatory response.…”
Section: Introductionmentioning
confidence: 99%